2019
DOI: 10.1111/jbi.13648
|View full text |Cite
|
Sign up to set email alerts
|

Is catchment geodiversity a useful surrogate of aquatic plant species richness?

Abstract: Aim Conserving freshwater biodiversity in a rapidly changing world requires updated planning schemes and research efforts. Geodiversity – the diversity of Earth surface forms, materials and processes – and biodiversity are interlinked at a fundamental level. This relationship is being considered in a growing number of studies, yet research from freshwater environments is scarce. We used geodiversity (rock‐type, soil‐type and geomorphological richness), local and climatic variables to explore whether geodiversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…Our results are congruent with previous studies about the importance of geodiversity variables in the terrestrial realm Bailey et al 2017;Tukiainen et al 2017a). Recently, Toivanen et al (2019) also reported a significant positive relationship between geodiversity variables and the species richness of aquatic plants in lakes and rivers. These findings also support our present results and encourage the inclusion of geodiversity variables in species richness models of several organismal groups in both terrestrial and aquatic realms.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are congruent with previous studies about the importance of geodiversity variables in the terrestrial realm Bailey et al 2017;Tukiainen et al 2017a). Recently, Toivanen et al (2019) also reported a significant positive relationship between geodiversity variables and the species richness of aquatic plants in lakes and rivers. These findings also support our present results and encourage the inclusion of geodiversity variables in species richness models of several organismal groups in both terrestrial and aquatic realms.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have also shown that biological communities in northern freshwater ecosystems are clearly affected by climate over broad areas, as has been observed for algae [433], macroinvertebrates [434], and fish [419]. Finally, land use, land cover, and catchment heterogeneity have been found to be associated with both alpha and beta diversity variation of macrophytes (e.g., [435]) and macroinvertebrates (e.g., [428]).…”
Section: Boreal and Arctic Freshwater Habitatsmentioning
confidence: 81%
“…This integrated view (Figure 3), to be achieved, might benefit from the theoretical foundations provided by approaches grounded in ecohydrogeology [84], catchment geodiversity (rock type, soil type, and geomorphological richness) as a basis to infer freshwater biodiversity facets [435], and increased recognition that healthy, diverse freshwater ecosystems provide vital natural functions at the landscape scale (e.g., [628]).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the tested predictors are proxies for other environmental variables (light, nutrients, photosynthesis). Nonetheless, the addition of other predictors that have been shown to influence species distribution, such as soil variables (Dubuis et al, ), geodiversity (Toivanen et al, ), land cover (Gallardo & Aldridge, ; Luoto, Virkkala, & Heikkinen, ), water temperature (Cianfrani, Satizábal, & Randin, ), human footprint (Rodríguez‐Merino, García‐Murillo, Cirujano, & Fernández‐Zamudio, ), or biotic interactions (Wisz et al, ), could improve predictive performance at least for some species. Using SDMs to explore the statistical relationship between species occurrences and environmental predictors is useful but has limitations, as models are an estimation of the fundamental niche based on the realized niche, as observed distributions are constrained by biotic interactions and limiting resources (Guisan & Thuiller, ).…”
Section: Discussionmentioning
confidence: 99%
“…For mean water chemistry values of samples collected during ice‐free period in all lakes and most streams ( n = 134), the number of individual samples varied among predictors and water bodies, ranging from three to 50 depending on local monitoring frequency. For 16 streams out of 150 surveyed in year 2016, the water chemistry values were single samples taken simultaneously with the plant surveys (see Rääpysjärvi et al, and Toivanen et al, for further details). Year‐to‐year variation in hydrology and water chemistry may have had some influence on mean water quality values when number of samples was low.…”
Section: Methodsmentioning
confidence: 99%